2012
DOI: 10.1016/j.micinf.2012.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioides brasiliensis induces secretion of IL-6 and IL-8 by lung epithelial cells. Modulation of host cytokine levels by fungal proteases

Abstract: Paracoccidioides brasiliensis is a pathogenic, dimorphic fungus that causes paracoccidioidomycosis, a systemic human mycosis that is highly prevalent in Latin America. In this study, we demonstrated that P. brasiliensis yeasts induced interleukin (IL)-8 and IL-6 secretion by human lung epithelial A549 cells. However, tumor necrosis factor-α and interferon-γ were undetectable in these cultures. Moreover, P. brasiliensis yeasts induced activation of p38 mitogen-activated protein kinase (MAPK), c-Jun NH(2)-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…Recently, Maza et al . () showed that P. brasiliensis extracellular proteases degrade proinflammatory cytokines. Therefore, host protease inhibitors would be an obvious defense mechanism by neutralizing fungal proteases involved in infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Maza et al . () showed that P. brasiliensis extracellular proteases degrade proinflammatory cytokines. Therefore, host protease inhibitors would be an obvious defense mechanism by neutralizing fungal proteases involved in infection.…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular proteases can play important roles in pathogenic fungal nutrition, tissue invasion, and host immune system evasion (Naglik et al, 2003). Recently, Maza et al (2012) showed that P. brasiliensis extracellular proteases degrade proinflammatory cytokines. Therefore, host protease inhibitors would be an obvious defense mechanism by neutralizing fungal proteases involved in infection.…”
Section: Resultsmentioning
confidence: 99%
“…13 Our results clearly demonstrate that renal epithelial cells are capable of initiating an immune response to fungal pathogens, similar to other epithelial cell types. 18,54,58,60,72 Interactions between renal epithelial cells and fungal cells, using a cell culture monolayer, showed that C. albicans formed hyphae and penetrated into M-1 epithelial cells at 3 h post-infection. C. albicans had previously been shown to adhere to the HEK293 human kidney cell line, but chemokine and cytokine responses were not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial cells, including renal cortical epithelial cells, are known to be capable of initiating an innate immune response through proinflammatory cytokine production, e.g., IL-8, IL-6, and IL-1. 22,[54][55][56][57][58][59][60][61] We, therefore, chose to evaluate murine renal epithelial cells as the basis for the development of a new assay to allow in vitro assessment of C. albicans virulence.…”
Section: Introductionmentioning
confidence: 99%
“…The level of IL-8 produced is observed to correlate with the severity of lung injury (9). Several studies have suggested that the overexpression of IL-8 is essential to the pathophysiological changes observed in chronic inflammatory lung disease (10,11). The level of IL-8 is reportedly a crucial prognostic factor for acute respiratory distress syndrome-associated mortality (12).…”
Section: Introductionmentioning
confidence: 99%